THE EFFECTIVENESS OF CONTENT BASED INSTRUCTION IN EFL CONTEXTS - Zakirova, Zulkhumor Zairjonovna (Educational Research in Universal Sciences, 2023)
Content-Based Instruction (CBI) is a context where language and content are taught simultaneously. It is closely linked with the cognitive approach to teaching foreign languages as the language is taught through meaning or in a meaningful context. The current article investigates the definitions of CBI provided by different authors. In addition, it discusses the features of this approach as well as its benefits in EFL classroom settings.